"I Make Here My Soil. I Make Here My Country.". Issue 2 (April 2015) - Fathi, Mastoureh
Abstract : This article discusses the complex and multilayered notion of class in the lives of Iranian women migrant doctors in Britain. Addressing classed identities in skilled migrants' lives and professional belonging, the article first examines the construction of foreignness and the problem of belonging for a groups of doctors and dentists who lived in different cities in Britain in 2009–11. Second, drawn from the first point, it discusses the notion of "deserving to belong." This article suggests that these highly political narratives should be read within an intersectional framework in order to understand the complex issues involved in the lives of skilled migrants.